Aspergers in love : couple relationships and family affairs - Aston, Maxine C. (Jessica Kingsley, 2003)
Asperger Syndrome (AS) has often been considered to be incompatible with love and relationships, but as the number of people who are diagnosed with the disorder increases, it is becoming apparent that people with AS can and do have full and intimate relationships. Comparing and contrasting both AS and non-AS partners' viewpoints, this book frankly examines the fundamental aspects of relationships that are often complicated by the disorder. With all findings illustrated with case examples taken f.